POLA DISTRIBUSI PENDERITA PENYAKIT PARU OBSTRUKTIF KRONIK DI RUANG RAWAT INAP RSU DOKTER SOEDARSO PONTIANAK - ., Dian Hariyanti (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Chronic Obstructive Pulmonary Disease (COPD) is achronic disease that characterized by air flow obstruction in respiratorytract that is not fully reversible. COPD is a major cause of chronicmorbidity and mortality throughout the world.Objective. The aims of the study were to obtained distribution pattern ofpatients with COPD according to age, sex and discharge from hospital incare units of dr. Soedarso General Hospital on 2009-2010 period.Method. This study was a descriptive study with cross-sectional design.Sample that used in this study was 86 patients. Data was taken from thepatient's medical record.Result. Group of more than 60 years old in age was the most commonwith 61 patients. The number of male patients are 71 patients and womenare 15 patients. The patients were discharged from the hospital are 65patients become better, 16 patients are home forcibly, and 5 patients aredied.Conclusion. The most common age group of patients with COPD whohave hospitalization in dr. Soedarso General Hospital is more than 60years old (70,93%), male (82,56%), and discharge from the hospital isbecome better (75,58%).Keyword : Chronic Obstructive Pulmonary Disease (COPD), age, sex,discharge from hospital